Removing the thermal component from heart rate provides an accurate V˙O2 estimation in forest work. (May 2016) - Dubé, Philippe-Antoine; Imbeau, Daniel; Dubeau, Denise; Lebel, Luc; Kolus, Ahmet
Abstract: Heart rate (HR) was monitored continuously in 41 forest workers performing brushcutting or tree planting work. 10-min seated rest periods were imposed during the workday to estimate the HR thermal component (Δ HR T ) per Vogt et al. (1970, 1973). V ˙ O 2 was measured using a portable gas analyzer during a morning submaximal step-test conducted at the work site, during a work bout over the course of the day (range: 9–74 min), and during an ensuing 10-min rest pause taken at the worksite. The V ˙ O 2 estimated, from measured HR and from corrected HR (thermal component removed), were compared to V ˙ O 2 measured during work and rest. Varied levels of HR thermal component (Δ HR T avg range: 0–38 bpm) originating from a wide range of ambient thermal conditions, thermal clothing insulation worn, and physical load exerted during work were observed. Using raw HR significantly overestimated measured work V ˙ O 2 by 30% on average (range: 1%–64%). 74% of V ˙ O 2 prediction error variance was explained by the HR thermal component. V ˙ O 2 estimated from corrected HR, was not statistically different from measured V ˙ O 2 . Work V ˙ O 2 can be estimated accurately in the presence of thermal stress using Vogt et al.'s method, which can be implemented easily by the practitioner with inexpensive instruments. Highlights: A practical application of Vogt et al.'s method to assess the HR thermal component during forest work is shown. The V ˙ O 2 overestimation error is strongly correlated to the thermal strain level observed. Vogt et al.'s method enabled an accurate estimation of the HR motor and thermal components. Removing the thermal HR component from the measured HR eliminated the overestimation error.